Implementing a best-practice model of gestational diabetes mellitus care in dietetics: a qualitative study - Shelley A. Wilkinson; Maxine O'Brien; Sally McCray; Desley Harvey (BMC, 2019)
Abstract Background Translating research into clinical practice is challenging for health services. Emerging approaches in implementation science recognise the need for a theory-driven approach to identify and overcome barriers to guideline adherence. However, many clinicians do not have the capacity, confidence, or expertise to realise change in their local settings. Recently, two regional sites participated in a facilitated implementation project of an evidence-based model of gestational diabetes mellitus (GDM) care in dietetics, supported by a team at a metropolitan centre. This study describes (i) stakeholder experiences', and (ii) learnings to inform implementation of the model of care (MOC) across Queensland. Methods This qualitative descriptive study utilised semi-structured telephone interviews with staff involved in implementation of the MOC project at two regional sites. Eight participants were recruited; five participants were from one site. Interviews were transcribed and analysed to identify recurrent themes. Results Four main themes were derived: (1) catalyst for positive change, (2) managing project logistics, (3) overcoming barriers, and (4) achieving change. Conclusions A model of external facilitated implementation using an evidence-based decision making tool is an effective method of fostering health service change and is acceptable to staff. Key elements of the facilitation were building confidence and capacity in local implementers, through regular contact, encouraging local networking, linking to higher management support and assessing and/or influencing workplace or organizational culture. However, the balance between delivering clinical care while participating in a service change project proved challenging to many participants.